Abusive Pediatric Burns Module in the Child Abuse Pediatrics Curriculum for Physicians (CAP-CuP) - Katie Johnson; Caitlin Crumm; Emily Brown (Association of American Medical Colleges, 2024)
Introduction Child abuse pediatrics is an underrepresented area of medical education. To date, the available teaching materials about child abuse in MedEdPORTAL do not address burn injury, and the available materials about burn injury do not address child abuse. We created an interactive, case-based module on abusive pediatric burns to fill this educational gap. Methods The abusive pediatric burns module was presented to a hybrid audience at a 45-minute emergency medicine grand rounds at Mayo Clinic. Participants completed a pre- and postmodule assessment to measure their confidence and knowledge pertaining to abusive pediatric burns. Results Fifty-six attendees, from an audience primarily composed of emergency medicine physicians but also including some multidisciplinary individuals, participated in the module. The median confidence level in assessing pediatric burns for abuse showed a modest increase from 4 (interquartile range [IQR]: 2-6) to 6 (IQR: 5-8), and the proportion of participants answering knowledge questions correctly increased for every question: 18% versus 45%, 41% versus 100%, 59% versus 84%, and 72% versus 100%. Qualitative feedback from the audience was favorable. Discussion This interactive, case-based module about abusive pediatric burns was successfully administered to an audience at emergency medicine grand rounds. Increases in confidence and knowledge were observed, and positive qualitative feedback was received.